Robust Distributed Formation Control for Heterogeneous UAVs-UGVs Systems: An Adaptive Asymptotic Funnel Control Approach - Yan, Yancheng; Liang, Hongjing; Cheng, Yuhua; Li, Tieshan (IEEE transactions on vehicular technology, 2025)
This paper is concerned with the distributed formation control problem of heterogeneous uncrewed aerial vehicles-uncrewed ground vehicles (UAVs-UGVs) systems, in the presence of practical factors such as parametric and dynamics uncertainties, external disturbances, coupled dynamics, and communication noises. First, we establish a model for the heterogeneous UAVs-UGVs system with such practical factors. Subsequently, a new robust distributed formation control strategy is developed. To be specific, by implementing a delicate transformation with a special funnel function, together with fusing an adaptive asymptotic funnel control approach, a funnel-based formation control strategy is constructed. In comparison to the current outcomes, this strategy demonstrates the subsequent salient characteristics: 1) enhancing the robustness of the considered system subject to such practical factors; 2) achieving the asymptotic formation control with predefined global funnel performance constraints; 3) lowering computational and structural complexity without function approximation, switching of the controller structure, and complex nonlinear terms. Ultimately, the theoretical assertions are validated via the simulation paradigm.